The Effects of Delayed Stabilization on Fracture Healing - Miclau, Theodore (2007)
Previous studies have revealed that delayed internal fixation can stimulate fracture callus formation and decrease the rate of non-union. However, the effect of delayed stabilization on stem cell differentiation is unknown. To address this, we created fractures in mouse tibiae and applied external fixation immediately, at 24, 48, 72, or 96 hours after injury. Fracture healing was analyzed at 10 days by histological methods for callus, bone, and cartilage formation, and the mechanical properties of the calluses were assessed at 14 days post-injury by tension testing. The results demonstrate that delaying stabilization for 24 to 96 hours does not significantly affect the volume of the callus tissue (TV) and the new bone (BV) that formed by 10 days, or the mechanical properties of the calluses at 14 days, compared to immediate stabilization. However, delaying stabilization for 24 to 96 hours induces 10–40 times more cartilage in the fracture calluses compared with fractures stabilized immediately. These findings suggest that delaying stabilization during the early phase of fracture healing may not significantly stimulate bone repair, but may alter the mode of bone repair by directing formation of more cartilage. Fractures that are not rigidly stabilized form significantly larger amount of callus tissues and cartilage by 10 days post-injury than fractures stabilized at 24 to 96 hours, indicating that mechanical instability influences chondrocytes beyond the first 96 hours of fracture healing.